Environmental technology adoption in many company - Rahimi Abidin; Che Sobri Abdullah; Wan Mohd Sabki Wan Omar (Universiti Teknologi MARA (UiTM), 2008)
Organized by Universiti Teknologi MARA (UiTM) Perlis , 5th - 7th December 2007 at Putra Palace Hotel, Kangar.